Genotypic variations in the plasticity of nodal root penetration through the hardpan during soil moisture fluctuations among four rice varieties. (3rd April 2018) - Nguyen, Dinh Thi Ngoc; Suralta, Roel Rodriguez; Kano-Nakata, Mana; Mitsuya, Shiro; Owusu-Nketia, Stella; Yamauchi, Akira
Abstract: Rainfed lowland rice fields are characterized by soil moisture fluctuations (SMF) and the presence of hardpan that impedes deep rooting and thus limits water extraction from deep soil layer during the periods of drought. In this study, we used rootboxes with three layers; shallow layer, artificial hardpan, and deep and wet layer below the hardpan, to evaluate differences in the plasticity of nodal roots elongation through the hardpan and promote root branching below the hardpan in response to SMF among four rice varieties; Sasanishiki, Habataki, Nipponbare, and Kasalath. Experiments were conducted during the summer and autumn seasons. Plasticity was computed as the difference in root traits within each variety between the SMF and continuously well-watered treatments. In both experiments, Habataki consistently tended to exhibit higher root plasticity than the other three varieties by increasing number of nodal roots that penetrated the hardpan during rewatering period in SMF, when the soil moisture increased and penetration resistance decreased. This root plasticity then contributed to greater water use at the deeper soil during the subsequent drought period and overall shoot dry matter production. Habataki had significantly higher δ 13 C value in roots at deep layer than roots at the shallow and hardpan layers under SMF, which may indicate that these were relatively newly grown roots as a consequence of root plasticity. This study also indicates that CSSLs derived from Sasanishiki and Habataki varieties may be suitable for the analysis of QTLs associated with root plasticity expression in rainfed lowland with hardpan and experiencing SMF.